Genetic Relationship among Indigenous Goat Populations in Nigeria based on Cellulose Acetate Electrophoresis Systems (2018)
Genetic diversity is the baseline for survivability and improvement of livestock in a wide array of environments. Variations among Red Sokoto, Sahel and WAD goats was determined using 5ml of blood collected by jugular venipuncture from 150 randomly selected goats (50 goats per breed). The samples were subjected to Cellulose Acetate Electrophoresis to determine the genetic variants of Haemoglobin (Hb), Transferrin, Carbonic Anhydrase, Albumin, Esterase 1, Esterase 3 and Alkaline phosphatase. Allele frequencies, similarity indices as well as genetic distances among the breeds were estimated. All the breeds in this study were polymorphic for Haemoglobin, Transferrin, Carbonic Anhydrase, Albumin, Alkaline phosphatase and Esterase 1 except WAD which was monomorphic for Alkaline phosphatase. The frequencies of HbA was considerably higher in Red Sokoto and WAD while frequencies of HbB were higher in Sahel goat population. The significant deviations from HWE (P<0.05, P<0.01 and P<0.001) was observed for some of the loci within the breeds. Genetic distance (D) obtained in this study ranged between 0.0648 and 0.1579 which indicates little genetic differentiation between the breeds. The results of this current study suggest that genetic improvement will be better achieved if WAD and Sahel goats are crossed.